Hubungan antara Self-Efficacy dan Goal Orientation dengan Self-Regulated Learning pada Siswa - Rizqi Fitriyani; Sugiyo (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to determine the relationship between self-efficacy and goal orientation with students' self-regulated learning at the Walisongo Islamic Junior High School. This research is a quantitative research with ex post facto design. The sample in this study was 158 students. The analysis of hypothesis testing in this study is a technique of partial correlation and multiple correlation. The results of the partial correlation analysis show that there is a significant positive relationship between self-efficacy and self-regulated learning and there is a significant positive relationship between goal orientation and self-regulated learning. The results of multiple correlation analysis show that there is a significant positive relationship between self-efficacy and goal orientation with self-regulated learning. Conclusion: the higher the self-efficacy and goal orientation, the higher the self-regulated learning. This shows that individuals who are able to determine clear learning goals and are able to increase confidence in their abilities, can formulate appropriate and effective learning strategies according to their abilities. Abstrak Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara self-efficacy dan goal orientation dengan self-regulated learning siswa di SMP Islam Walisongo. Penelitian ini merupakan penelitian kuantitatif dengan desain ex post facto. Sampel dalam penelitian ini sebanyak 158 siswa. Analisis pengujian hipotesis dalam penelitian ini adalah teknik korelasi parsial dan korelasi ganda. Hasil analisis korelasi parsial menunjukkan bahwa terdapat hubungan positif yang signifikan antara self-efficacy dengan self-regulated learning dan terdapat hubungan positif yang signifikan antara goal orientation dengan self-regulated learning . Hasil analisis korelasi ganda menunjukkan bahwa terdapat hubungan positif yang signifikan antara self-efficacy dan goal orientation dengan self-regulated learning. Kesimpulan: semakin tinggi self-efficacy dan goal orientation maka semakin tinggi pula self-regulated learning. Hal tersebut menunjukkan bahwa individu yang mampu menentukan tujuan belajar yang jelas dan mampu meningkatkan keyakinan terhadap kemampuan yang dimiliki, maka individu tersebut dapat merumuskan strategi belajar tepat dan efektif sesuai kemampuan dirinya.